Pelatihan Deteksi Lesi Periapikal Berbasis CNN–LSTM Retinex untuk Diagnosis Radiografis Dokter Gigi - Safar Dwi Kurniawan; David Bani Adam (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
Accurate periapical lesion diagnosis represents a significant clinical challenge for dentists, particularly in primary care clinics with limited access to Computer-Aided Diagnosis (CAD) systems. This Community Service (PKM) program aims to train dental medical personnel in using an AI-based periapical lesion detection system integrating CNN–LSTM architecture with Retinex image enhancement. The program was conducted at Primary Dental Clinics in the City Region over three months (October–December 2024), involving 32 dentists and 8 radiographers. Methods included socialization, intensive workshops, clinical case simulations, and technical mentoring. Evaluation results showed an average competency score increase of 34.7% (from 61.2 to 82.4 out of 100), with 87.5% of participants successfully operating the system independently. Participant satisfaction reached 89.1% (very satisfied category). The implemented AI system achieved periapical lesion detection accuracy of 98.4% with 97% recall, far exceeding manual diagnosis sensitivity averages of 70–85%. This PKM demonstrates that AI diagnostic technology transfer to primary dental clinical practitioners is feasible and significantly impacts dental healthcare quality improvement